Etymological observations (մուկն, ունկն, ականջ-(ք)) - Petrosyan, Vardan (Bulletin of Yerevan University B: Philology, 2021)
Starting from H. Hubschmann an Armenian origin has been ascribed to the sound (ն - n) of the Armenian words which make rhymes with the sonorant- ն (n) (ակն, արմուկն, բեւեկն, դալուկն, ծունկն, ձուկն, մուկն, ունկն, etc.) and the proceeding -k- voiceless fricative. Henceforth, -կ-was considered a word forming particle, namely an augment. The present etymological investigation attempts to demonstrate that this claim is not fully convincing, at least in case of the sound – կ- in words մուկն, ունկն and the plural form of the latter - ականջ-(ք). The -կ- in the words mentioned is a root element and represents the IE occlusive phoneme *s. The initial (=root) version of the մուկն was * մուկ, which, like other IE languages – Greek, Latin, Indian, Iranian, Slavic, Lithuanian, stems from the IE prototype *mūs. The original root of the word ունկն was *ուկ-, and that of ականջ - *ակ. From the typological perspective, the transition from the IE *s>Arm. կ (k) is grounded by the fact that in some of the languages mentioned above *s is represented by the back-lingual voiceless fricative х [x] (Ancient Slavic, Rus.) ḫ [x] (Hittite), and also by voiceless occlusive κ (k) - ἀκούω “to hear” in Greek like in Armenian. Initially, the word ականջ served as the form of the dual number of the word ունկն. Similarly, the word “աչ” acted as the dual number of ակն (an eye). The sound -ն- (n)- in the word * ունկ appeared as a result of a change of sounds within a word. The sound - ջ – in the word ականջ-(ք), in most probability, was the result of the analogy between the sing. Nouns in Genitive-Dative cases (comp. գիւղ, կին, այգի, կղզի, տարի, etc. ) and the with forms in Locative Case ending in – ջ (comp. գեղջ «գյուղի», կնոջ «կնոջ», (յ)այգւոջ «այգու(ն)/այ¬գում», (ի) կղզւոջ «կղզու(ն)/կղզում», (ի) տարւոջ «տարվա /տա¬րում», etc.). The word մուկ, like in all IE languages, derives from the IE prototype *mūs, while *ուկ- and *ակ- stem from the prototypes *aus- or *ōus- * through the dropping of -u or the monophthongisation of the diphthong(s) *au/*ōu.
Keywords: մուկն; ունկն; Indo European prototypes; dialectal forms; ն sonorant rhyme; voiceless fricatives